Analisis Perbandingan Pembentukan Komponen Cadangan Dengan Wajib Militer Korea Selatan Sebagai Upaya Bela Negara Dalam Sistem pertahanan Dan Keamanan Negara (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
The 1945 Constitution of the Republic of Indonesia stipulates that Indonesian citizens must participate in efforts to defend the country. This is contained in article 27 paragraph 3 which reads, "Every citizen has the right and obligation to participate in efforts to defend the country". Developing and attitude of defending the country can be done with several efforts, such as providing compulsory military education which has been implemented in several countries such as South Korea. Basic military training in Indonesia is only given to Indonesian National Soldiers, which in essence is something that is directly related to the profession they are undertaking. This journal seeks to explain how the public perceives the implementation of military service in Indonesia the form of a komponen cadangan (komcad) as part of the country’s defense and security system.